Novel Quinolone Substituted Imidazol-5(4H)-ones as Anti-inflammatory, Anticancer Agents: Synthesis, Biological Screening and Molecular Docking Studies - Kumar, Santosh; Aghara, Jignesh C; Manoj, Anirudh; Alex, Angel T; A, Jesil Mathew; Joesph, Alex (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Quinolones and imidazolones are important heterocyclic moieties which have been reported to possess potent anti-inflammatory and anticancer properties. The activity of these compounds were related to inhibition of nuclear factor-kappaB (NF- κB) which is one of the important targets studied for designing of anti-inflammatory and antitumor drugs. Further, hybrid pharmacophore approach is used in the present study for designing potent molecules. Objectives: Aim of the study is to synthesis a series of quinolone substituted imidazolones and evaluation of their anti-inflammatory and anticancer activity. Methods: Quinolone substituted imidazolones were synthesized by aminolysis of 7-amino-4-methyl-quinoline-2(1H)-one with substituted oxazolones afforded quinolone substituted imidazolones. Structures of synthesized compounds were characterized by spectral techniques and were evaluated for anti-inflammatory activity by carrageenan-induced rat paw oedema test. Differences between control and treatment groups were tested using one way analysis of variance followed by Tukey’s test. Anticancer activity was assessed by evaluating the cytotoxicity of compounds on BT-549 and HeLa, human cancer cell lines by MTT assay. Results: Compounds 3-fluorobenzylidene substituted imidazolonyl quinolone (F3) and 4-phenoxybenzylidene substituted imidazolonyl quinolone (F12) were the most cytotoxic compounds against BT-549 and HeLa cell lines. While 2-chlorobenzylidene substituted imidazolonyl quinolone (F4) and 4-chlorobenzylidene substituted imidazolonyl quinolone (F5) exhibited the highest anti-inflammatory activity. Most of the test compounds exhibited statistically significant inhibition of paw oedema volume when compared to that of control. Conclusion: Molecular docking studies revealed that combination of two pharmacophores was crucial for binding of quinolone substituted imidazol-5(4H)-ones on NF-κB with good correlation between docking score and biological activity.
Keywords: Anti-inflammatory; Anticancer; Docking; Quinolone; Imidazolone; NF-κB